Peranan lembaga konsultasi dan bantuan hukum dalam proses penanganan serta penyelesaianperkara tindak pidana di Yogyakarta - Yohanes Masudede; Fransisca Romana Harjiyatni; Eko Nurharyanto (Kajian Hasil Penelitian Hukum, 2019)
The provision of legal assistance in criminal cases is one of the important things that must be given to every disadvantaged society but in reality this often becomes a problem in the lives of people who cannot afford it, therefore this study aims to 1To know the role The Institute for Legal Consultation and Assistance in cases of criminal acts that occur. 2 To find out what constraints faced by the Legal Consultation and Aid Agency in handling and resolving cases of crimes that occur. This study uses a normative method which refers to the application of legal norms or norms. The research was carried out using the literature approach and legislation, then analyzed the data using qualitative analysis methods, namely data sourced directly from the field which will then be presented descriptively. In helping disadvantaged people, the role of the Institute for Consultation and Legal Aid has not been carried out optimally because it is still constrained by human resources that are not yet sufficient in several Legal Aid and Consultation Institutions this is of course important to be noticed together by all parties, because the purpose of the presence of the Legal Consultation and Assistance Agency through Law No. 16 of 2011 concerning Legal Aid is to help poor people for free.